Quantifying adsorption‐induced deformation of nanoporous materials on different length scales. Issue 5 (14th September 2017) - Morak, Roland; Braxmeier, Stephan; Ludescher, Lukas; Putz, Florian; Busch, Sebastian; Hüsing, Nicola; Reichenauer, Gudrung; Paris, Oskar
Abstract : Simultaneous small‐angle neutron scattering and dilatometry reveal water‐adsorption‐induced deformation of silica materials with hierarchical porosity along with their adsorption isotherm. Abstract : A new in situ setup combining small‐angle neutron scattering (SANS) and dilatometry was used to measure water‐adsorption‐induced deformation of a monolithic silica sample with hierarchical porosity. The sample exhibits a disordered framework consisting of macropores and struts containing two‐dimensional hexagonally ordered cylindrical mesopores. The use of an H2 O/D2 O water mixture with zero scattering length density as an adsorptive allows a quantitative determination of the pore lattice strain from the shift of the corresponding diffraction peak. This radial strut deformation is compared with the simultaneously measured macroscopic length change of the sample with dilatometry, and differences between the two quantities are discussed on the basis of the deformation mechanisms effective at the different length scales. It is demonstrated that the SANS data also provide a facile way to quantitatively determine the adsorption isotherm of the material by evaluating the incoherent scattering contribution of H2 O at large scattering vectors.